Effects of Ketamine 0.5 mg/kgBW administration as preemptive analgesia on analgesia duration and the need for Fentanyl following hysterectomy surgery: a randomized controlled trial - I. Fuadi; A. Zulfariansyah; Jacklin Edward Mokoginta (Вестник интенсивной терапии)
INTRODUCTION: Hysterectomy is a surgical procedure with a high number of moderate to severe postoperative pain complications. Preemptive analgesia prevents central sensitization before surgery, hampering postoperative hyperesthesia. Ketamine is one of several preemptive analgesia available. This study aims to study the effects of ketamine 0.5 mg/kgBW administration as preemptive analgesia on analgesia duration and the need for fentanyl following hysterectomy surgery. MATHERIALS AND METHODS: This study is a double-blind randomized controlled trial experiment on two groups: the treatment group (n = 20) was given ketamine 0.5 mg/kgBW and the control group (n = 20). The duration was measured starting from surgery completion up to the need for additional fentanyl 25 µg analgesia through Patient Controlled Analgesia (PCA) within 24-hour periods following surgery. Numerical data statistical analysis was done using unpaired T-test and Mann—Whitney for normally distributed data and non-normally distributed data respectively. Categorical data statistical analysis was done using the Exact Fisher test. RESULTS: The mean time recorded until additional analgesia was needed in the treatment group was 246.00 ± 33.150 minutes and in the control group was 121.50 ± 23.792 minutes. The mean total 24-hour post-surgery additional analgesia was 82.50 ± 11.75 µg and 118.75 ± 11.10 µg for the treatment group and control group respectively. There were statistically significant differences in the duration of analgesia and the need for additional analgesia between the two subject groups (p < 0.05). CONCLUSIONS: Administration of ketamine preemptive analgesia at a dose of 0.5 mg/kgBW resulted in longer analgesia duration and reduced the need for fentanyl as an additional analgesic in postoperative patients compared with no preemptive analgesia and showed no significant side effects.